2018
DOI: 10.1002/jssc.201701228
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the transformation of ginsenosides in Ginseng Radix et Rhizoma during decoction with water using ultra‐fast liquid chromatography coupled with tandem mass spectrometry

Abstract: This study was conducted to determine the variations of ginsenosides in Ginseng Radix et Rhizoma when using different preparation solvents and explore the major factors for changes. With an established ultra-fast liquid chromatography coupled with tandem mass spectrometry method which could quantify 52 ginsenosides, the extraction differences were characterized and compared using different solvents (water, 70% aqueous ethanol, and ethanol). Subsequently, a series of aqueous solutions with different pH were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…S3, † S3 and Table S1 †) were corresponded to the successively neutral losses of rhamnose (146.0585 Da) and glucose (162.0529 Da), which were coincided with the previously reported fragmentation information from the pseudo-ginsenoside F 11 . 34 By comparison their accurate mass measurements of MS 2 spectrum with previous literature reports, peak 88, 129 and 131 were tentatively iden-tied as ginsenoside Rg1, ginsenoside Rf and pseudoginsenoside F 11 , respectively, 35 and further conrmed with reference compounds. Other examples of distinguishing isomers by diagnostic ions were shown in the ESI.…”
Section: Ion Mobility and Ccs Prediction For Isomers Annotationmentioning
confidence: 75%
See 1 more Smart Citation
“…S3, † S3 and Table S1 †) were corresponded to the successively neutral losses of rhamnose (146.0585 Da) and glucose (162.0529 Da), which were coincided with the previously reported fragmentation information from the pseudo-ginsenoside F 11 . 34 By comparison their accurate mass measurements of MS 2 spectrum with previous literature reports, peak 88, 129 and 131 were tentatively iden-tied as ginsenoside Rg1, ginsenoside Rf and pseudoginsenoside F 11 , respectively, 35 and further conrmed with reference compounds. Other examples of distinguishing isomers by diagnostic ions were shown in the ESI.…”
Section: Ion Mobility and Ccs Prediction For Isomers Annotationmentioning
confidence: 75%
“…Both of peak 88 and 129 generated common fragment ions at m / z 637.4318 [M − H − glc] − , 475.3784 [M − H − 2glc] − and 391.2796 [M − H − 2glc − C 6 H 12 ] − , indicating that they belong to PPT-type and contain two glucose. 35 Characteristic fragment ion at m / z 221.0689 [2glc − H − C 4 H 8 O 4 ] − , an indicative of disaccharide residue, could only be detected in peak 129. The fragment ions of peak 131 at m / z 653.4365 and m / z 491.3800 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have reported the ginsenoside concentrations from China and Korea. However, they mainly focused on one batch or limited batches of sample analysis [16,17,18]. There are few studies concerning the comparison of ginsenosides between ginseng grown in different countries.…”
Section: Resultsmentioning
confidence: 99%
“…Certain derivatives of those glycosides such as malonyl and acetyl ginsenosides were also identified in ginseng. A large number of natural ginsenosides and processed ginsenosides were reported in studies that include (a) the evaluation of the type and level of ginsenosides in various types of ginseng such as Korean ginseng ( Panax ginseng ), South China ginseng ( Panax notoginseng ), American ginseng ( Panax quinquefolius ), as well as other types such as Siberian ginseng ( Eleuterococcus senticous ), Vietnamese or Japanese ginseng [1], (b) distribution of ginsenosides in different parts of the Panax plant [2, 3], (c) composition of ginsenosides in different ginseng preparations [4–6], and (d) the level of ginsenosides in biological fluids [7–11]. Regarding the analytical methodology for ginsenosides analysis, several techniques such as thin layer chromatography, capillary electrophoresis, gas chromatography, and enzyme immunoassay were reported, but the most common separation technique used for the analysis is HPLC.…”
Section: Introductionmentioning
confidence: 99%